THE RECONSTRUCTION OF KAIDAH AL-TAZKÎR AND AL-TA’NÎS IN PARADIGM OF GENDER EQUALITY INTERPRETATION - Halya Millati (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2020)
The rules of al-tazkîr and al-ta'nîs (masculinity and femininity) formulated by classical interpretation don’t adhere to the principle of equality. This is triggered by exclusivity of men as a necessity of applying these rules, which causes superiority of male (muzakkar) and inferiority of women (mu'annas). This paper aims to illustrate the rules of al-tazkîr and al-ta'nîs in the classical period, how the current reconstruction was, and what motives inspired the reconstruction. With Thomas Kuhn's theory of scientific revolution, this literature research finds that the rule of al-tazîr and al-ta'nîs was originally adopted from Arabic grammar, and it’s full of male superiority. Then, experiencing a shift, which was initially partial because it was only oriented towards language, into a theory of equality with its various forms that were more responsive to women. The theories chronologically include maqasid musawah (Ibn 'Ashur, w. 1973), the reciprocal theory of the Prophet's hadith (Abu Shuqqah, w. 1995), and Qira'ah Mubadalah (Faqihuddin Abdul Kodir). In addition, the motive for this shift is that the rule of al-tazkîr and al-ta'nîs is unable to answer the problem of gender inequality, so reconstruction efforts need to be carried out..